Comparison of two staining methods for the detection of nucleolar organizing regions (NOR) of acrocentric chromosomes - Rosas-Cartolin, Berioska (2023)
This study aimed to compare two staining methods for detecting nucleolar organizing regions (NOR) of acrocentric chromosomes in the Cytogenetics Laboratory of INMP (“Instituto Nacional Materno Perinatal”), Lima, Peru.  A total of 60 metaphases with normal karyotypes were analyzed, of which 30 were stained for each method: Kodama et al. and Howell & Black, respectively. The recognition efficiency and staining intensity of these regions were evaluated by each technique based on the count of NORs Ag (+); Likewise, the staining and integrity of the chromosomes were evaluated and the differences between these two methods were established. No significant differences were found regarding the number of stained regions with both techniques; however, in staining intensity and chromosomal quality, the Howell & Black method was superior. It is concluded that the Howell & Black method generates better results for the cytogenetic analysis of these regions.